2018
DOI: 10.1111/jcmm.13597
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: MicroRNA‐140‐5p elevates cerebral protection of dexmedetomidine against hypoxic–ischaemic brain damage via the Wnt/β‐catenin signalling pathway

Abstract: Hypoxia–ischaemia (HI) remains a major cause of foetal brain damage presented a scarcity of effective therapeutic approaches. Dexmedetomidine (DEX) and microRNA‐140‐5p (miR‐140‐5p) have been highlighted due to its potentially significant role in the treatment of cerebral ischaemia. This study was to investigate the role by which miR‐140‐5p provides cerebral protection using DEX to treat hypoxic–ischaemic brain damage (HIBD) in neonatal rats via the Wnt/β‐catenin signalling pathway. The HIBD rat models were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…For example, miR-7a-5p was demonstrated to therapeutically reduce the brain damage and disability caused by ischemic stroke [37]. Additionally, consistent with the observations of our study, miR-140-5p has been highlighted due to its promotion role in the cerebral protective effects of dexmedetomidine against hypoxic-ischemic brain damage (HIBD) in neonatal rats [38]. Furthermore, there is existing data that suggests that miR-140-5p suppresses the tumor growth and progression of hepatocellular carcinoma, tongue cancer, and cervical cancer [28,39,40].…”
Section: Discussionsupporting
confidence: 88%
“…For example, miR-7a-5p was demonstrated to therapeutically reduce the brain damage and disability caused by ischemic stroke [37]. Additionally, consistent with the observations of our study, miR-140-5p has been highlighted due to its promotion role in the cerebral protective effects of dexmedetomidine against hypoxic-ischemic brain damage (HIBD) in neonatal rats [38]. Furthermore, there is existing data that suggests that miR-140-5p suppresses the tumor growth and progression of hepatocellular carcinoma, tongue cancer, and cervical cancer [28,39,40].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, knockdown of miR-140-5p decreased the expression of Cleaved Caspase-3 and increased the expression of Bcl-2 to inhibit hippocampal neuronal apoptosis in diabetic rats with isoflurane anesthesia. Wnt1 was identified as a target of miR-140-5p in neonatal rats for cerebral protection (Han et al, 2018) or in dental pulp stem cells for odontoblastic differentiation (Lu et al, 2019). In the present study, SNX12 was identified as a new target of miR-140-5p.…”
Section: Discussionsupporting
confidence: 49%
“…MiR-140-5p was identified as a tumor suppressor in gastric cancer (Fang et al, 2017), and regulates odontoblastic differentiation (Lu et al, 2019). More recently, miR-140-5p was shown to protect against hypoxic-ischaemic brain damage via promotion of learning and memory abilities (Han et al, 2018). In addition, a study has shown that miR-140-5p was increased 6 hr after isoflurane treatment (Luo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, such effect is diminished when the 3′UTR of the Wnt1 sequence is mutated. Consistently, Han et al revealed that miR-140-5p could target and inhibit the Wnt1 gene, thus highlighting the negative regulation of the Wnt/β-catenin signaling pathway in hypoxia [21].…”
Section: Discussionmentioning
confidence: 74%